(untitled) (Politeja, 2023)
CLASSICAL ELITE THEORY AND THE CONCEPT OF THE DEEP STATE: RESEARCH OUTLOOK ON THE EXAMPLES OF TURKEY AND ITALY This paper is an attempt to clarify the relationship between the elite theory and the idea of the deep state. Both approaches address similar questions about how concentrated political power is created in the state, and both offer similar answers. An analysis of the historical context based on Italian and Turkish experiences with deep-state entities like mafia and intelligence agencies helps us understand dysfunctional elites in action. Consequently, the article explores research possibilities and theoretical solutions combining elitists view of politics with historical data.